NLRP3 Plays a Critical Role in the Development of Experimental Autoimmune Encephalomyelitis by Mediating Th1 and Th17 Responses - Gris, Denis (2010)
The interplay between innate and adaptive immunity is important in multiple sclerosis (MS). The inflammasome complex, which activates caspase-1 to process pro–IL-1β and pro–IL-18, is rapidly emerging as a pivotal regulator of innate immunity, with nucleotide-binding domain, leucine-rich repeat containing protein family, pyrin domain containing 3 (NLRP3) (cryopyrin or NALP3) as a prominent player. Although the role of NLRP3 in host response to pathogen associated molecular patterns and danger associated molecular patterns is well documented, its role in autoimmune diseases is less well studied. To investigate the role of NLRP3 protein in MS, we used a mouse model of MS, experimental autoimmune encephalomyelitis (EAE). Nlrp3 expression was elevated in the spinal cords during EAE, and Nlrp3(−/−) mice had a dramatically delayed course and reduced severity of disease. This was accompanied by a significant reduction of the inflammatory infiltrate including macrophages, dendritic cells, CD4, and CD8(+) T cells in the spinal cords of the Nlrp3(−/−) mice, whereas microglial accumulation remained the same. Nlrp3(−/−) mice also displayed improved histology in the spinal cords with reduced destruction of myelin and astrogliosis. Nlrp3(−/−) mice with EAE produced less IL-18, and the disease course was similar to Il18(−/−) mice. Furthermore, Nlrp3(−/−) and Il18(−/−) mice had similarly reduced IFN-γ and IL-17 production. Thus, NLRP3 plays a critical role in the induction of the EAE, likely through effects on capase-1–dependent cytokines which then influence Th1 and Th17.